Perceived Social Support Promotes Nursing Students’ Psychological Wellbeing: Explained With Self-Compassion and Professional Self-Concept - Zhou, Lu; Sukpasjaroen, Khunanan; Wu, Yuming; Gao, Liu; Chankoson, Thitinan; Cai, Enli (Frontiers in Psychology, 2022)
Background: The psychological distress of nursing students is ongoing and getting worse during the COVID-19 outbreak. Numerous calls for future research on exploring the effects of perceived social support on nursing students’ mental health. However, the pathway(s) between perceived social support and psychological well-being remain unknown. Objectives: To explore how self-compassion and professional self-concept mediate the relationship between perceived social support and psychological well-being to explain the theoretical mechanisms of the relation. Design: An analytical cross-sectional research based on online self-reports and completed validated measures of perceived social support, psychological well-being, self-compassion and professional self-concept. Methods: The Structural Equation Model (SEM) was used to estimate the mediation effects on the relationship between perceived social support and psychological well-being. In order to examine the directionality of effects, the present study also tested the reverse serial mediation model. Multi-group SEM was used to test gender differences in the mediation model. Results: The results of an empirical study involving 487 undergraduate nursing students verified an integrative model of social support. In addition, no gender difference was found in these associations. These findings suggest that self-compassion and professional self-concept accounted for the association between perceived social support and psychological well-being, and self-compassion was a significant predictor of professional self-concept. Conclusions: The pathway of self-compassion and professional self-concept through which perceived social support may improve psychological well-being. And improving nursing students’ perceived social support, self-compassion and professional self-concept are beneficial for promoting their mental health. It is meaningful for nursing educators to take measures to develop nursing students’ psychological well-being and enhance their professional self-concept.